Depression among outpatients with diabetic peripheral neuropathy: prevalence and associated factors - Besher Gharaibeh; Aya Baniyones; Sawsan Abuhammad; Amat Al-Khaleq O Mehrass (Future Science OA)
Aim This study aims to assess the prevalence of depression among patients with diabetic neuropathy and identify contributing factors.Methods A cross-sectional descriptive design was used, recruiting 153 patients from outpatient clinics. Participants completed the Beck Depression Inventory II, Michigan Neuropathy Screening Instrument, and Douleur Neuropathique 4 questionnaires, with recent A1C results obtained from medical records.Results The mean depression score was 16.5, with 98 patients (65%) reporting depression and 20 (13%) indicating moderate to severe depression. Approximately half of the sample experienced neuropathy and neuropathic pain. The mean Michigan Neuropathy Screening Instrument score was 5 (SD = 5), and the Douleur Neuropathique 4 score was 4 (SD = 3.5). Regression analyses showed significant demographic influences on depression. Higher Michigan Neuropathy Screening scores predicted greater depression severity, while DN4 scores did not significantly impact depression levels.Conclusions Depression in patients with diabetic neuropathy is influenced by the severity of neuropathy. Factors commonly associated with depression in diabetes, such as pain intensity and glycemic control, do not significantly affect depression in the context of neuropathy. These findings highlight the complexity of addressing depression in diabetes care, requiring comprehensive and ongoing approaches.